The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1063/1.1379585
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent quantum wave packet study of the C+CH reaction

Abstract: The quantum dynamics of the CϩCH reaction has been studied by means of time-dependent quantum wave packet calculation on 1AЈ potential energy surface. Initial state-specific total reaction probabilities and integral cross section are calculated, and the rate constants obtained are in reasonably good agreement with experimental measurement. Although a deep well is present in the potential surface, no long-lived resonances are found from the dynamics calculation and the reaction proceeds by a direct mechanism, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…However, experimental work concerning the kinetics of the title reaction is very rare, with only three estimated values of the rate constant reported in the literature and databases [3][4][5]. Some theoretical calculations [6][7][8][9][10] have been carried out on the title reaction. The three-dimensional time-dependent wave-packet method [11,12] was applied to study the dynamics of the reaction C þ CH on 1 2 A 0 PES [9] and 2 2 A 0 PES [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental work concerning the kinetics of the title reaction is very rare, with only three estimated values of the rate constant reported in the literature and databases [3][4][5]. Some theoretical calculations [6][7][8][9][10] have been carried out on the title reaction. The three-dimensional time-dependent wave-packet method [11,12] was applied to study the dynamics of the reaction C þ CH on 1 2 A 0 PES [9] and 2 2 A 0 PES [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical calculations [6][7][8][9][10] have been carried out on the title reaction. The three-dimensional time-dependent wave-packet method [11,12] was applied to study the dynamics of the reaction C þ CH on 1 2 A 0 PES [9] and 2 2 A 0 PES [10]. Those studies showed that the results of the quantum calculation corroborate the QCT results of Rayez and coworkers [8].…”
Section: Introductionmentioning
confidence: 99%
“…While there is, to the best of our knowledge, no experimental work concerning the kinetics of the C + CH reaction, there are some theoretical calculations on the title reaction. [5][6][7][8][9] Tang et al have carried out quantum calculations on the adiabatic 1A and 2A electronic states, respectively, employing the time-dependent wave packet (TDWP) method, 5,6 and have evaluated the corresponding cross sections and rate constants by the J-shifting approximation. Boggio-Pasqua et al 7 have performed a quasi-classical trajectory (QCT) study of the title reaction on the three lowest adiabatic potential energy surfaces (PESs) constructed by themselves, yielding the corresponding cross sections and rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…20,[26][27][28] The time-dependent quantum wave packet method has been used to study the reaction C + CH by Tang et al 20 Han et al 1,[7][8][9][11][12][13][14][15][16][17][18][19] have developed the QCT method to investigate the product rotational polarization of bimolecular reactions. In the present work, the QCT method has been utilized to investigate the reaction C + CH and explore the stereo-dynamics feature of the reaction on the three lowest potential energy surfaces (PESs) reported by Boggio-pasqua et al 26,29 The four PDDCSs and the three angular distributions of P (θ r ), P (φ r ), P (θ r , φ r ) at a fixed collision energy 0.1 eV have been calculated.…”
Section: Introductionmentioning
confidence: 99%